PESANTREN DAN BUDAYA KEPENULISAN - Yahya Aziz (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2011)
This study aims to describe and analyze the implementation of Practical Journalism as media development potential of students in boarding school student Hashim Ash'ari Yogyakarta. The results showed: (1) Practical Journalism schools are activities that are categorized as semi-autonomous schools curriculum that aims to develop the potential of students of authorship in the media. Learning methods used are lecture-dialogue-assignment. Strategy adopted there are three things: provoke the onset of motivation to write the first and second introducing practical theories (which are directly related to the practice), and a third practice and actualization of the work. (2) efforts to develop the potential of authorship through Practical Journalism can be said to succeed termuatnya reflected in the writings of the students in various media, whether it is national or local scale. With this success, indirectly from the boarding schools have done improfisasi methodology and combines the elements of job-related skills (vocational) with scientific development.